Hemodynamic effects of target-controlled infusion of propofol alone or in combination with a constant-rate infusion of remifentanil in dogs - Beier, Suzane L.; Mattoso, Cláudio R. S.; Aguiar, Antonio J. A.; Vianna, Pedro T. G. [UNESP]; Massone, Flavio (My University, 2015)
The objective of this study was to evaluate the hemodynamic effects of target-controlled infusion (TCI) of propofol alone or in combination with a constant-rate infusion (CRI) of remifentanil. Six adult dogs were given 2 treatments in a randomized crossover study with a 7-day interval between treatments. Treatment 1 was propofol (P) and treatment 2 was propofol and remifentanil (P-Rem), without any premedication. Propofol was induced using a TCI system with a predicted plasma concentration (Cp) of 6.0 mg/mL. Anesthesia was maintained within the Cp range (0.65 to 3.0 mg/mL) for 120 min and remifentanil was administered at a rate of 0.3 mg/kg body weight (BW) per minute, CRI. Cardiopulmonary variables were recorded before (baseline), during, and 120 min after drug administration. Heart rate (HR) decreased significantly in the P-Rem group (46%) compared with baseline values. In the P-Rem group, the cardiac index (CI) decreased significantly (49% to 58%) and the stroke volume (SV) decreased compared with baseline values. The systemic vascular resistance index (SVRI) increased significantly in the P-Rem group compared with baseline values. There was no difference in mean arterial pressure (MAP) between the groups. Central venous pressure (CVP) and pulmonary artery occlusion pressure (PAOP) significantly increased in the P-Rem group compared with baseline values. In conclusion, the hemodynamic changes observed in this study indicate a compromise of the cardiovascular system, although the dogs in this study were healthy/euvolemic and there was no change in preload. More studies are required in order to evaluate the actual safety of the combination of propofol and remifentanil in patients with reduced cardiac reserve.